Natural gas geological characteristics and great discovery of large gas fields in deep-water area of the western South China Sea - Zhenfeng Wang; Zhipeng Sun; Jitian Zhu; Minggang Guo; Rufeng Jiang (Natural Gas Industry B, 2015)
To accelerate the petroleum exploration in deep sea of China, since the period of “the 11th Five-Year Plan”, the sedimentary process, source rock formation and hydrocarbon generation and expulsion process in deep-water area of the Qiongdongnan Basin in the western South China Sea have been studied systematically using the data like large-area 3D seismic survey, logging, drill core (cuttings) and geochemical analysis, providing three innovative understandings, i.e. excellent hydrocarbon source conditions, good accumulation conditions, and grouping and zonal distribution of large exploration targets. From the study, the following conclusions are drawn. First, the deep-water area located in the southern and central parts of the Qiongdongnan Basin was formed under the control of such tectonic events as Indosinian–Eurasian Plate collision, Himalayan uplifting and South China Sea expansion, and experienced Paleogene lift and Neogene depression stages. Second, accompanied by lacustrine deposition, faulting activity was violent in Eocene; whereas in Early Oligocene, rift continued to develop under a sedimentary environment of marine–terrestrial transitional facies and littoral-neritic facies. Third, oil generation predominated Eocene lacustrine mudstone and gas generation predominated Lower Oligocene marine–terrestrial transitional facies coal-measure strata compose two sets of major source rocks. Fourth, analysis in respect of thermal evolution level, hydrocarbon generation volume and hydrocarbon generation intensity shows that Ledong, Lingshui, Baodao and Changchang sags belong to potential hydrocarbon-rich kitchens, among which Ledong and Lingshui sags have been proved to have great hydrocarbon generation potential by drilling. Fifth, researches of deep-water sedimentology and hydrocarbon accumulation dynamics reveal that Paleogene and Neogene plays are developed vertically, and favorable hydrocarbon accumulation zones like the Central Canyon lithologic trap zone (group), Changchang circum-sag trap zone (group) and southern Baodao fault terrace zone are developed horizontally in the area. Sixth, with its excellent petroleum accumulation conditions and great exploration potential, the Central Canyon lithologic trap zone should be taken as the preferred drilling target, which has been verified correct by the discovery of the Central Canyon Gas Field — the largest gas field in the northern South China Sea.